Induced Pluripotent Stem Cell‐Derived Endothelial Cells Overexpressing Interleukin‐8 Receptors A/B and/or C‐C Chemokine Receptors 2/5 Inhibit Vascular Injury Response. (24th February 2017) - Giordano, Samantha; Zhao, Xiangmin; Chen, Yiu‐Fai; Litovsky, Silvio H.; Hage, Fadi G.; Townes, Tim M.; Sun, Chiao‐Wang; Wu, Li‐Chen; Oparil, Suzanne; Xing, Dongqi
Abstract: Recruitment of neutrophils and monocytes/macrophages to the site of vascular injury is mediated by binding of chemoattractants to interleukin (IL) 8 receptors RA and RB (IL8RA/B) C‐C chemokine receptors (CCR) 2 and 5 expressed on neutrophil and monocyte/macrophage membranes. Endothelial cells (ECs) derived from rat‐induced pluripotent stem cells (RiPS) were transduced with adenovirus containing cDNA of IL8RA/B and/or CCR2/5. We hypothesized that RiPS‐ECs overexpressing IL8RA/B (RiPS‐IL8RA/B‐ECs), CCR2/5 (RiPS‐CCR2/5‐ECs), or both receptors (RiPS‐IL8RA/B+CCR2/5‐ECs) will inhibit inflammatory responses and neointima formation in balloon‐injured rat carotid artery. Twelve‐week‐old male Sprague‐Dawley rats underwent balloon injury of the right carotid artery and intravenous infusion of (a) saline vehicle, (b) control RiPS‐Null‐ECs (ECs transduced with empty virus), (c) RiPS‐IL8RA/B‐ECs, (d) RiPS‐CCR2/5‐ECs, or (e) RiPS‐IL8RA/B+CCR2/5‐ECs. Inflammatory mediator expression and leukocyte infiltration were measured in injured and uninjured arteries at 24 hours postinjury by enzyme‐linked immunosorbent assay (ELISA) and immunohistochemistry, respectively. Neointima formation was assessed at 14 days postinjury. RiPS‐ECs expressing the IL8RA/B or CCR2/5 homing device targeted the injured arteries and decreased injury‐induced inflammatory cytokine expression, neutrophil/macrophage infiltration, and neointima formation. Transfused RiPS‐ECs overexpressing IL8RA/B and/or CCR2/5 prevented inflammatory responses and neointima formation after vascular injury. Targeted delivery of iPS‐ECs with a homing device to inflammatory mediators in injured arteries provides a novel strategy for the treatment of cardiovascular diseases. Stem Cells Translational Medicine 2017;6:1168–1177